ISO 22000 certification: diffusion in Europe - Granja, Nathalia (2021)
The main aim of this paper is to answer the research question, “Is the Gompertz model suitable for studying the diffusion of the ISO 22000 standard in Europe?” Forecasting models adopting the Gompertz model were developed to estimate to which extent the Food Safety Management Systems (FSMS) based on the ISO 22000 standard are expected to be implemented and certified in the European continent. To provide a forecast for the next few years, data from the diffusion of renowned ISO standards, namely, ISO 9001 and ISO 14001, were extrapolated in order to overcome the shortcoming since data concerning ISO 22000 certification was only available for the period 2007 to 2018. The results provide a cross-sectional portrayal of the European diffusion of ISO 22000 certification and suggest an interval of the estimated number of certificates issued in Europe. This research paper presents the first attempt to empirically analyze the dynamic of diffusion of the European ISO 22000 certification. A more accurate fitting with real results may be expected with further information available in the forthcoming years.